2021
DOI: 10.1038/s41598-021-86268-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and oxidative stress induce sterile placental inflammation in vitro

Abstract: Fetal growth restriction (FGR) and stillbirth are associated with placental dysfunction and inflammation and hypoxia, oxidative and nitrative stress are implicated in placental damage. Damage-associated molecular patterns (DAMPs) are elevated in pregnancies at increased risk of FGR and stillbirth and are associated with increase in pro-inflammatory placental cytokines. We hypothesised that placental insults lead to release of DAMPs, promoting placental inflammation. Placental tissue from uncomplicated pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 75 publications
1
34
0
Order By: Relevance
“…This is the same sign of inflammation that is exhibited by hibernating brown bears during torpor [ 48 ], except that in brown bears it is manifested by elevated serum levels of haptoglobin and β-macroglobulin [ 61 ]. Moreover, the levels of IL-1β and TNFα in placental tissues are increased and the relative anti-inflammatory factor IL-10 is reduced after placental hypoxia in humans [ 62 ]; similarly, the present study also found a reduction in IL-10 level during torpor in ground squirrels ( Figure 2 C). There is also evidence indicating that markers of inflammation-related damage are increased in some hibernating tissues during torpor [ 63 , 64 , 65 ], which may be reversible upon arousal [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 83%
“…This is the same sign of inflammation that is exhibited by hibernating brown bears during torpor [ 48 ], except that in brown bears it is manifested by elevated serum levels of haptoglobin and β-macroglobulin [ 61 ]. Moreover, the levels of IL-1β and TNFα in placental tissues are increased and the relative anti-inflammatory factor IL-10 is reduced after placental hypoxia in humans [ 62 ]; similarly, the present study also found a reduction in IL-10 level during torpor in ground squirrels ( Figure 2 C). There is also evidence indicating that markers of inflammation-related damage are increased in some hibernating tissues during torpor [ 63 , 64 , 65 ], which may be reversible upon arousal [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 83%
“…Virtually all placental cell types are sources of oxidative stress, including trophoblasts, endothelial cells in the placenta, Hofbauer macrophages, or stromal cells in the villi [153]. The sustained hypoxia leads to excessive inflammation and oxidative stress, two closely related conditions [154,155]. Furthermore, excessive oxidative stress may lead to a disruption in different placental cells, affecting some critical events, such as apoptosis or autophagy, participating in the pathogenesis of PE [156].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Growing evidence also suggests that endogenous inflammatory mediators such as danger-associated molecular patterns (DAMPs) may contribute to this inflammation and its consequences ( Menon et al, 2016b ; Padron et al, 2020 ). Oxidative stress and hypoxia in the placenta cause the production of several DAMPs, including; uric acid, high mobility group box1 (HMGB1), S100 calcium-binding protein A (S100A), S100 calcium binding protein alpha-12 (S100A12), heat shock protein (HSP) 70 kD, and cell-free fetal DNA (cffDNA) ( Baker et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%